2020
DOI: 10.1007/s11242-020-01396-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Electrolyte Distribution in Technical Gas Diffusion Electrodes: From Imaging to SPH Simulations

Abstract: The performance of the gas diffusion electrode (GDE) is crucial for technical processes like chlorine-alkali electrolysis. The function of the GDE is to provide an intimate contact between gaseous reactants, the solid catalyst, and the liquid electrolyte. To accomplish this, the GDE is composed of wetting and non-wetting materials to avoid electrolyte breakthrough. Knowledge of the spatial distribution of the electrolyte in the porous structure is a prerequisite for further improvement of GDE. Therefore, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The microstructure of the GDEs shows silver grains with deposited PTFE at their grain boundaries and a complex open pore system extending through the whole electrode (Figure 7). Previous investigations showed that this microstructure is homogenous over the whole cross section of the GDE [22]. Moreover, the laboratory X-ray radiographies and the FIB cuts demonstrate that large pores with sizes of about 40 µm form regularly between the Ni mesh (Figure 2).…”
Section: Discussionmentioning
confidence: 73%
“…The microstructure of the GDEs shows silver grains with deposited PTFE at their grain boundaries and a complex open pore system extending through the whole electrode (Figure 7). Previous investigations showed that this microstructure is homogenous over the whole cross section of the GDE [22]. Moreover, the laboratory X-ray radiographies and the FIB cuts demonstrate that large pores with sizes of about 40 µm form regularly between the Ni mesh (Figure 2).…”
Section: Discussionmentioning
confidence: 73%
“…Comparing the graded electrode with the highest silver loading (45 mg Ag cm −2 ) and the full silver electrode, there is still a significant difference in the limiting current density. This proves, that the active part of the full silver electrode is thicker than 75 μm and thus the electrolyte must intrude much deeper than expected from other simulation approaches [15–17] . Unfortunately, the electrolyte penetration depth cannot be determined exactly for the full silver electrode and will only be revealed by operando tomography experiments.…”
Section: Discussionmentioning
confidence: 88%
“…This proves, that the active part of the full silver electrode is thicker than 75 μm and thus the electrolyte must intrude much deeper than expected from other simulation approaches. [15][16][17] Unfortunately, the electrolyte penetration depth cannot be determined exactly for the full silver electrode and will only be revealed by operando tomography experiments. Nevertheless, we proved experimentally and with our model-based analysis that large parts of the full silver GDE are intruded by the electrolyte and are utilized for the ORR in high alkaline media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations